2019
DOI: 10.1109/toh.2018.2864751
|View full text |Cite
|
Sign up to set email alerts
|

A Tactile Computer Mouse for the Display of Surface Material Properties

Abstract: We present a novel input/output device to display the tactile properties of surface materials. The proposed Tactile Computer Mouse (TCM) is equipped with a series of actuators that can create perceptually relevant tactile cues to a user. The display capabilities of our TCM match the major tactile dimensions in human surface material perception, namely, hardness, friction, warmth, microscopic roughness, and macroscopic roughness. The TCM also preserves necessary interaction capabilities of a typical computer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Figure 6 shows a recent approach of combining all five tactile dimensions into a single output device. The Tactile Computer Mouse (TCM) described in [82] enhances the input capabilities of a common computer mouse with additional actuators which are used to change the friction between the TCM and the underlying pad, display macroscopic roughness cues by changing the inclination of the upper mouse body, generate microscopic roughness impressions using voice coil actuators, simulate thermal flow using Peltier elements, and generate different hardness perceptions.…”
Section: Combinations Of Tactile Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 shows a recent approach of combining all five tactile dimensions into a single output device. The Tactile Computer Mouse (TCM) described in [82] enhances the input capabilities of a common computer mouse with additional actuators which are used to change the friction between the TCM and the underlying pad, display macroscopic roughness cues by changing the inclination of the upper mouse body, generate microscopic roughness impressions using voice coil actuators, simulate thermal flow using Peltier elements, and generate different hardness perceptions.…”
Section: Combinations Of Tactile Dimensionsmentioning
confidence: 99%
“…6: Presentation of the five major tactile dimensions (upper plot) on a computer mouse-like tactile display (lower left). The Tactile Computer Mouse described in [82] uses several actuators to display surface material properties. It has been shown that this device is able to represent the five major tactile dimensions in a real -virtual material comparison test and that subjects were able to identify 10 virtual surfaces (VS0 to VS9) using this device absent visual and audible information (lower right confusion plot).…”
Section: Waveform-based Representation and Compression Of Tactile Sigmentioning
confidence: 99%
“…The disadvantage is that the stimulating touch of the dot matrix raised plate feedback is limited, so it is only suitable for the recognition of distinct object image shapes. Strese et al developed a tactile mouse that can display the material properties of an object [5]. It mainly relies on the sensor hardware's judgment of the local data set and the real‐time interaction is poor.…”
Section: Related Workmentioning
confidence: 99%
“…The pattern was realized by a hybrid electromagnetic-pneumatic actuation and the temperature is controlled by a Peltier element. More recently, Strese et al [7] presented a tactile mouse to display the hardness, friction, warmth and roughness of virtual objects. The hardness, friction and roughness were actuated by the electromagnet, servo and voice coil actuator, and the thermal stimuli were created by a Peltier element.…”
Section: Introductionmentioning
confidence: 99%